Phlebotomus papatasi sand fly predicted salivary protein diversity and immune response potential based on in silico prediction in Egypt and Jordan populations. - Catherine M Flanley; Marcelo Ramalho-Ortigao; Iliano V Coutinho-Abreu; Rami Mukbel; Hanafi A Hanafi; Shabaan S El-Hossary; Emadeldin Y Fawaz; David F Hoel; Alexander W Bray; Gwen Stayback; Douglas A Shoue; Shaden Kamhawi; et al. (Public Library of Science (PLoS), 2020)
Phlebotomus papatasi sand flies inject their hosts with a myriad of pharmacologically active salivary proteins to assist with blood feeding and to modulate host defenses. In addition, salivary proteins can influence cutaneous leishmaniasis disease outcome, highlighting the potential of the salivary components to be used as a vaccine. Variability of vaccine targets in natural populations influences antigen choice for vaccine development. Therefore, the objective of this study was to investigate the variability in the predicted protein sequences of nine of the most abundantly expressed salivary proteins from field populations, testing the hypothesis that salivary proteins appropriate to target for vaccination strategies will be possible. PpSP12, PpSP14, PpSP28, PpSP29, PpSP30, PpSP32, PpSP36, PpSP42, and PpSP44 mature cDNAs from field collected P. papatasi from three distinct ecotopes in the Middle East and North Africa were amplified, sequenced, and in silico translated to assess the predicted amino acid variability. Two of the predicted sequences, PpSP12 and PpSP14, demonstrated low genetic variability across the three geographic isolated sand fly populations, with conserved multiple predicted MHCII epitope binding sites suggestive of their potential application in vaccination approaches. The other seven predicted salivary proteins revealed greater allelic variation across the same sand fly populations, possibly precluding their use as vaccine targets.